Realization of Circular Slot Frequency Selective Surfaces using Photoplotter and Wet Etching Technique for Terahertz Material Sensing Applications - Ishak, N. S.; Dahri, M. Hashim; Awang, N .A.; Chong, W. Y.; Seman, F. C. (International Journal of Integrated Engineering, 2020)
This paper discusses on the analysis of band pass Frequency Selective Surfaces (FSS) for performance enhancement in material sensing application. Terahertz Spectroscopy has proved to be versatile tool for detection and sensing in measuring non-conductive materials. It is because most of the non-conductive materials have unique molecular resonance that may translate as transmission and absorption of signals within terahertz range. However, the most critical issue in detection and sensing is to improve its sensitivity therefore an extremely low concentration material still can be able to be detected in THz band. Hence, in this paper, a circular slot is modeled on a planar structure of Rogers Duroid 5880LZ substrate with thickness of 508Âµm using Computer Simulation Technology (CST). The simulation generates a band pass response with transmission magnitude of 0.95 at 0.66THz. Furthermore, photoplotter and wet etching fabrication process is used for the realization of terahertz FSS. Simulated and measured transmission shows a good agreement between 0.5THz to 0.7THz as only 1% shifts in frequency between simulated and measured results. Besides that, the fabrication of circular FSS shows narrower measured bandwidth as compared to its simulated counterpart. Hence, with the limitation of the wet etching to produce micron size structure both simulation and measured result shows good agreement for all the critical issues in this study.